Sample size requirement in trials that use the composite endpoint major adverse cardiovascular events (MACE): new insights - Josep Ramon Marsal; Iratxe Urreta-Barallobre; Marimar Ubeda-Carrillo; Dimelza Osorio; Blanca Lumbreras; David Lora; Borja M. Fernández-Felix; Gerard Oristrell; Eduard Ródenas-Alesina; Lorena Herrador; Mónica Ballesteros; Javier Zamora; et al. (Trials, 2022)
Abstract Background The real impact of the degree of association (DoA) between endpoint components of a composite endpoint (CE) on sample size requirement (SSR) has not been explored. We estimate the impact of the DoA between death and acute myocardial infarction (AMI) on SSR of trials using use the CE of major adverse cardiac events (MACE). Methods A systematic review and quantitative synthesis of trials that include MACE as the primary outcome through search strategies in MEDLINE and EMBASE electronic databases. We limited to articles published in journals indexed in the first quartile of the Cardiac & Cardiovascular Systems category (Journal Citation Reports, 2015–2020). The authors were contacted to estimate the DoA between death and AMI using joint probability and correlation. We analyzed the SSR variation using the DoA estimated from RCTs. Results Sixty-three of 134 publications that reported event rates and the therapy effect in all component endpoints were included in the quantitative synthesis. The most frequent combination was death, AMI, and revascularization (n = 20; 31.8%). The correlation between death and AMI, estimated from 5 trials¸ oscillated between − 0.02 and 0.31. SSR varied from 14,602 in the scenario with the strongest correlation to 12,259 in the scenario with the weakest correlation; the relative impact was 16%. Conclusions The DoA between death and AMI is highly variable and may lead to a considerable SSR variation in a trial including MACE.